Property rights and the making of Christendom - KINGSTON, WILLIAM (Hamline University School of Law, 1992)
The benefits of efficient laws of property are obtained by altruism in their formulation, which is able to deal with self-interest in action within them.
PUBLISHED
Keywords: property rights; religion